Tax Evasion and its Effects on the Economy - Khanal, Madhav (JMC Research Journal, 2019)
Tax evasion happens when individuals, organization or agency purposely do not adhere to their tax obligation. The loss of tax revenue caused by tax evasion seriously hampers the proper functioning of the public sector by creating problems in its ability to finance its expenses. The study investigates the opinion of the tax professionals regarding the tax evasion in Nepal with the focus on the factors responsible for the tax evasion and possible remedies to decrease the problem of tax evasion. The main objective of the study is to identify the causes of income tax evasion and assess the impact of tax evasion in Nepal. To collect the information regarding tax evasion in Nepal a well-designed questionnaire with five-point Likert scale has been used. Their opinion reveals that high tax rates, corruption in public sector units, multiple tax rates and inefficient tax authorities are the main causes of tax evasion in Nepal.